Isolation and characterization of antioxidative and cytotoxic phytoconstituents from Aegle marmelos (L.) Correa and Murraya koenigii (L.) Spreng. and their in silico study - Ng, Rou Chian (2019)
Rutaceae family includes Aegle marmelos and Murraya koenigii had been used as medicinal plants since ancient to treat fever, snake bites, diarrhoea and stomachache. However, scientific validation of medicinal properties on Aegle marmelos and Murraya koenigii are still limited. In this research, two Rutaceae plants namely Murraya koenigii (curry leaves tree) and Aegle marmelos (majapahit) were selected for the investigation of their phytochemicals, antioxidant and cytotoxicity properties. The mechanism of cytotoxic will be evaluated by in silico docking study. The isolation of phytoconstituents from Aegle marmelos yielded aegeline (7), two coumarins: marmin (33) and 7-hydroxycoumarin or umbelliferone (36) together with two triterpenoids : β-sitosterol (55) and epi-lupeol (31). Meanwhile, phytochemical constituents isolated from Murraya koenigii afforded four alkaloids including girinimbine (1), mahanimbine (45), murrayanine (49), murrayacine (44) and β- sitosterol (55). The chloroform extract of Murraya koenigii stem bark showed the highest antioxidant activity in CUPRAC (1490.89 mgTE/g extract). Mahanimbine (45) was the most active compound with the activity of 927.73 mgTE/g, and 1649.31 mgTE/g based on ABTS and CUPRAC assays respectively. It also showed lipid peroxidation inhibition with the percentage of 70.95%. The CUPRAC and ABTS results are the first report for Malaysian Murraya koenigii species. Cytotoxicity study revealed that the chloroform root extract of Murraya koenigii showed the most active (IC50: 11.26 ± 0.74 μg/mL) against MDA-MB-231, whilst, hexane root extract of Murraya koenigii show the most cytotoxic against MCF-7 (IC50:15.13 ± 2.37 μg/mL). Girinimbine (1) and mahanimbine (45) were found to exhibit potent cytotoxic activities toward MCF-7 with the IC50 values of 11.95 ± 3.63 μg/mL and 11.01 ± 0.48 μg/mL respectively. Girinimbine (1) also exhibited the most significant cell growth inhibition against MDA-MB-231, followed by mahanimbine (45) with IC50 of 8.92 ± 0.03 μg/mL and 12.41 ± 0.61 μg/mL, respectively. Cell death morphology studies revealed that both breast cancer cell lines treated with girinimbine (1) and mahanimbine (45) showed apoptotic characteristics such as cell shrinkage, nuclear condensation and membrane blebbing. Both girinimbine (1) and mahanimbine (45) were non-cytotoxic in the MTT cytotoxic screening against 3T3 cell lines (IC50> 30 μg/mL). The in silico docking studies of girinimbine (1), mahanimbine (45), murrayanine (49) and murrayacine (44) revealed that mahanimbine (45) showed the highest binding energy with the values of -9.31 and -9.30 kcal/mol towards p38α MAPK and hER-α receptors respectively. Meanwhile, docking of girinimbine (1) with p38α MAPK and hER-α receptors produced the binding energies of -8.60 and -8.83 kcal/mol respectively. The binding of both girinimbine (1) and mahanimbine (45) showed mutual interactions with the amino acids that responsible for the p38α MAP kinase inhibition. The hydrophobic interaction involved protein residues of Leu167, Lys53, Val30 and Val38. Meanwhile, the binding of girinimbine (1) and mahanimbine (45) showed anti-estrogen properties through the hydrophobic interaction with the amino acids such as Arg394, Glu353, Met421, Leu525, Ala350, Leu387, Leu349 and Leu391. The in silico studies of girinimbine (1) and mahanimbine (45) with p38α MAPK and hER-α were firstly reported. The in silico studies revealed that girinimbine (1) and mahanimbine (45) could be the potent drug nuclei as an anti-estrogen agent in the treatment of ER+ breast cancer and p38α MAP kinase inhibitor. The results suggested that girinimbine (1) and mahanimbine (45) which was isolated from Murraya koenigii could be potential candidates for breast cancer treatment and therapy.